2012
DOI: 10.1161/circresaha.112.268276
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Normalizes Hepatic Triglyceride-Rich VLDL Secretion by Triggering the CNS in High-Fat Fed Rats

Abstract: Rationale: Dysregulation of hepatic triglyceride (TG)-rich very low-density lipoproteins (VLDL-TG) in obesityand type 2 diabetes contributes to the dyslipidemia that leads to cardiovascular morbidity. The central nervous system (CNS), particularly the hypothalamus, regulates hepatic lipid metabolism. Although the underlying neurocircuitry remains elusive, glycine has been documented to enhance CNS N-methyl-D-aspartate (NMDA) receptor-mediated transmission.Objective: We tested the hypothesis that glycine regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
2
35
0
1
Order By: Relevance
“…N-methyl-D-aspartate (NMDA) receptor-mediated transmission in the DVC is sufficient and necessary for MBH nutrient sensing to lower glucose production 42,43 and is also sufficient to lower hepatic VLDL-TG secretion 27 . To begin delineating the neurocircuitry that mediates the lipid-lowering effect of MBH oleic acid sensing (Fig.…”
Section: Mbh K Atp -Channel Activation Lowers Vldl-tg Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-methyl-D-aspartate (NMDA) receptor-mediated transmission in the DVC is sufficient and necessary for MBH nutrient sensing to lower glucose production 42,43 and is also sufficient to lower hepatic VLDL-TG secretion 27 . To begin delineating the neurocircuitry that mediates the lipid-lowering effect of MBH oleic acid sensing (Fig.…”
Section: Mbh K Atp -Channel Activation Lowers Vldl-tg Secretionmentioning
confidence: 99%
“…Hypothalamic neuropeptide Y infusion augments VLDL-TG secretion 23,24 and impairs the ability of insulin to inhibit VLDL-TG secretion 25 . In contrast, glucose sensing in the mediobasal hypothalamus (MBH) 26 and glycine in the dorsal vagal complex (DVC) 27 suppress hepatic secretion of VLDL-TG. To date, the neurocircuitry involved in the central control of lipid homeostasis, as well as the ability of fatty acids to trigger a negative-feedback neuronal network to regulate hepatic VLDL-TG secretion, remain largely unknown.…”
mentioning
confidence: 99%
“…Thus, the above work defined the role of hypothalamic SUR1-containing K ATP channels in modulating hepatic gluconeogenesis and suggested that central insulin mediates its effect on EGP via vagal nerve efferent signaling to the liver (12). Recent work has also implicated extra-hypotha- http://www.jbc.org/ Downloaded from lamic brain regions, such as the dorsal vagal complex, in regulating whole body glucose and lipid handling, and identified novel signaling pathways (26,27).…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…Thus, the above work defined the role of hypothalamic SUR1-containing K ATP channels in modulating hepatic gluconeogenesis and suggested that central insulin mediates its effect on EGP via vagal nerve efferent signaling to the liver (12). Recent work has also implicated extra-hypotha- http://www.jbc.org/ Downloaded from lamic brain regions, such as the dorsal vagal complex, in regulating whole body glucose and lipid handling, and identified novel signaling pathways (26,27).The mechanism whereby central insulin suppresses EGP appears to be via phosphorylation of hepatic signal transducer and activator of transcription 3 (STAT3) (28 -30). Mice with liver-specific STAT3 deficiency are insulin-resistant with increased gluconeogenic enzyme expression, whereas constitutive hepatic STAT3 activation improves glucose tolerance in diabetic mice (29).…”
mentioning
confidence: 99%
“…16 Emerging evidence has also suggested that the sympathoinhibitor neurotransmitter nitric oxide (NO) [17][18][19] and the sympathoexcitatory neurotransmitter glutamate, through N-methyl-d-aspartate receptor (NMDAr), [20][21][22][23] play a role on energy metabolism. Recent data have shown that central lipid infusion by the carotid artery deregulates hepatic insulin signaling in rats, in part, by increasing neuronal NO synthase (nNOS) activity in hypothalamus, suggesting that nNOS in the hypothalamus might be involved with the development of insulin resistance.…”
mentioning
confidence: 99%